Análise das propriedades de medida da versão traduzida e adaptada do fibromyalgia rapid screening tool (FiRST) em português brasileiro - Sousa, Ana Paula de (2022)
Introduction: Fibromyalgia syndrome (FS) is a prevalent disease mainly in women and its diagnosis is basically clinical; therefore, tools that can execute the initial screening of the disease to help in the quick and simple screening and detection are necessary. This study performed the translation, crosscultural adaptation and validation for the Brazilian population of the screening tool “Fibromyalgia Rapid Screening Tool” (FiRST). Methods: The process of translation and cross-cultural adaptation was carried out in accordance with current guidelines and applied to 20 people with fibromyalgia in a pre-test phase so that it could later be used to validate the final version. After that, a total sample of 483 people who were selected according to the inclusion criteria responded to the instruments: final version of the FiRST, Numerical Scale for pain and fatigue intensity, Brief Pain Inventory (BPI) and the Fibromyalgia Impact Questionnaire-Revised (FIQ-R). The instrument’s validity was based on the comparison whit the ACR 2016 diagnostic criterion, using the properties of measures that included cross-cultural adaptation, test-retest reability and criterion validity. Result: The final sample consisted of 483 participants (81,8% cases of fibromyalgia) separated into groups with and without fibromyalgia. For test-retest reliability, 39 people with fibromyalgia participated, included in the total sample of evaluation 1. The two groups differed on pain characteristics (intensity, severity, impact), as well as on the domains of function, global impact and FS related symptoms. FiRST was able to discriminate patients with and without fibromyalgia. Criterion validity was acceptable as the area under the curve (AUC) was 0.819 (95% confidence interval = 75 to 88%; SE: 0.033, p<0.001), with a cutoff ≥ 5, the instrument showed 92.3% sensitivity and 61.6% specificity. Test-retest reliability was adequate with an ICC of 0.593 with a standard error of measurement (SEM) of 0.54 and least detectable change (SDC) of 0.24. Conclusion: The Brazilian version of the FiRST is a valid and reliable rapid screening tool for identifying patients with fibromyalgia for clinical or research use.